(untitled) (Research, Society and Development, 2023)
Violet-blue light is emitted by several electronic equipment such as computers, tablets, and smartphones. This light stimulates various brain regions and interferes with the natural functioning of the organism. Objectives: to evaluate the consequences of screen time on the sleep quality of students from the public school João de Paula Ribeiro. Methodology: the present article is a quantitative study, held through three online questionnaires that were applied to the students. The first questionnaire was elaborated by the authors and contains sociodemographic variables. To identify the sleep quality among the students, the Pittsburgh Sleep Quality Index (PSQI). The person responsible for each student that participated in the research authorized their participation by filling the Informed Consent Form. Results: of the 57 students that participated in the research, 33,3% spend more than 6h in front of the screen (tablet, cellphone, computer, television, etc.). Although only 19,3% of the students classified their sleep quality as “bad” or “very bad”, about 26% had difficulties on sleeping because they could not fall asleep in less than 30 minutes, and it happened three times or more in a week. Conclusion: longer exposure to screens leads to greater harm in aspects related to sleep, with disorders as insomnia and excessive daytime sleepiness; therefore, these aspects lead to serious cognitive and academic impairment.